2017
DOI: 10.21767/1307-234x.1000140
|View full text |Cite
|
Sign up to set email alerts
|

Rotten thallus of Red Seaweed, Gracilariopsis heteroclada Zhang et Xia, is Associated with Agar-Digesting Bacillus spp

Abstract: Abstract:Agar-digesting bacteria have been hypothesized to cause rottening of the thalli of economically important marine red seaweeds, Gracilariopsis heteroclada Zhang et Xia (Gracilariaceae, Rhodophyta). However, characterization of these causative agents accompanying seaweeds' disease in the marine environment has been poorly elucidated. Thus, agar-digesting bacteria associated with 'rottening thallus' of red seaweed, were isolated and characterized. Agar-digesters were selected based on their ability to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Syafitri et al (2017) revealed that on molecular characterization, the disease on this kind of algae mainly by bacteria which comes from the genera of Alteromonas, Bacillus, Pseudomonas, Pseudoalteromonas, Glaciecola, Aurantimonas, and Rhodococcus. Bacillus was found as agar-digester by forming a clear depression around their colony and/or liquefaction of agar on Gracilariopsis heteroclite (Martinez and Padilla, 2017). In…”
Section: Isolation and Identification Of Bacteriamentioning
confidence: 99%
“…Syafitri et al (2017) revealed that on molecular characterization, the disease on this kind of algae mainly by bacteria which comes from the genera of Alteromonas, Bacillus, Pseudomonas, Pseudoalteromonas, Glaciecola, Aurantimonas, and Rhodococcus. Bacillus was found as agar-digester by forming a clear depression around their colony and/or liquefaction of agar on Gracilariopsis heteroclite (Martinez and Padilla, 2017). In…”
Section: Isolation and Identification Of Bacteriamentioning
confidence: 99%